2021
DOI: 10.3390/ijerph18020639
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Binational Framework for Active and Healthy Ageing (AHA) Bridging Austria and Slovenia in a Thermal Spa Region

Abstract: In view of ongoing demographic developments resulting in a longer life expectancy of the European population, the creation of “age-friendly” environments represents an initiative picked up by the European Union and its Member States to enable active and healthy ageing. The present study aims at the co-creation of a cross-border framework model to deploy a healthy ageing region linking Austria and Slovenia, building on previous work dealing with the development of an integrated regional ecosystem for active and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…If on the one hand, it is necessary to understand the territorial development to identify the endogenous attributes and resources of a thermal destination, on the other hand, through relationship management, central and local government as well as local private investors need to co-operate and gather synergies through organisational communication (Duman and Kozak, 2010; Heung and Kucukusta, 2013; Huijbens, 2011; Lee et al , 2009; Liberato et al , 2020; Lindner et al , 2021; Noviello and Smętkiewicz, 2019; Pillmayer et al , 2020; Ponte et al , 2020; Smith, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…If on the one hand, it is necessary to understand the territorial development to identify the endogenous attributes and resources of a thermal destination, on the other hand, through relationship management, central and local government as well as local private investors need to co-operate and gather synergies through organisational communication (Duman and Kozak, 2010; Heung and Kucukusta, 2013; Huijbens, 2011; Lee et al , 2009; Liberato et al , 2020; Lindner et al , 2021; Noviello and Smętkiewicz, 2019; Pillmayer et al , 2020; Ponte et al , 2020; Smith, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Through communication. The major challenges for communication, given the current situation of the on-going Covid-19 pandemic, with travel restrictions severely affecting the tourism sector, mean that innovation and digital transformation are now more important than ever (Lindner et al , 2021). Besides making processes more agile and efficient, the digital age speeds up the spread of information, virtually in real time, social networks, websites, chatbots, booking, payments, shopping, all online, just by having an active Internet connection (Saura et al , 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Health is an important sector of the economy, and health tourism is growing rapidly across Europe. Health tourism refers to any form of tourism development related to health creation that includes health promotion, specific health services, or services addressing health needs related to specific conditions ( 49 ). An effective approach needs integration between health, social, and tourism services to make tourist destinations accessible, addressing the different pattern of needs: frailty, dependency, health-specific needs that determine spending priorities of significant parts of the general consumer economy, such as the “Silver Economy” ( 47 ).…”
Section: Transferable Elementsmentioning
confidence: 99%
“…observed that tourists in these destinations are interested in ancient traditions and rituals, natural resources and therapies, exclusive treatments and services that reflect the locality, important considerations for creating experiences, a destination brand and consequently loyalty. Finally,Beriatos and Papageorgiou (2008),Beriatos and Papageorgiou (2009),Duman and Kozak (2010),Heung and Kucukusta (2013),Huijbens (2011), Lindner et al (2021), Liberato et al (2020,Lee et al (2009), Noviello and Smętkiewicz (2019), Beriatos (2011), Pillmayer et al (2020),Smith (2015) andPonte et al (2020) investigate factors, resources and products, they sought to determine the attractiveness of a country for the Territorial Development of a thermal destination.…”
mentioning
confidence: 99%